2011
DOI: 10.1128/jcm.01280-11
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophyte Identification Using Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: The performance of the Bruker Biotyper matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometer (MS) for the identification of dermatophytes from clinical cultures was compared to that of dermatophyte identification using 28S rRNA gene sequencing. The MALDI Biotyper library (MBL; version 3.0) was used alone and in combination with a supplemented library containing an additional 20 dermatophyte spectra (S-MBL). Acquired spectra were interpreted using both the manufacturer-recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 27 publications
4
83
1
9
Order By: Relevance
“…Previous studies have shown that MALDI-TOF MS is a rapid and accurate method for the identification of dermatophytes. There have been many studies examining this group of molds, with identification rates of Ͼ90% for these studies (12,13,(20)(21)(22). Our study correctly identified 100% (14/14) of the dermatophytes tested.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that MALDI-TOF MS is a rapid and accurate method for the identification of dermatophytes. There have been many studies examining this group of molds, with identification rates of Ͼ90% for these studies (12,13,(20)(21)(22). Our study correctly identified 100% (14/14) of the dermatophytes tested.…”
Section: Discussionmentioning
confidence: 55%
“…Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp. or the dermatophytes (12,13,(19)(20)(21)(22)(23)(24)(25)(26). In our study, which examined 319 isolates from 43 different genera, the Vitek MS version 3.0 library was able to correctly identify 66.8% of isolates and 76.8% of the isolates after additional SARAMIS analysis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…D ermatophytes in the genera Epidermophyton, Microsporum, and Trichophyton are usually characterized and identified by cultural and morphological characters and physiological tests or, more recently, by sequencing (1). Morphological identification is time-consuming and complex, usually requiring expert mycological knowledge, while sequencing is comparatively expensive and at least 2 to 3 days elapse before sequencing results are available.Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a reliable technique for the identification and typing of microbial pathogens such as bacteria (2-7), yeasts (8-10), and filamentous fungi, including dermatophytes (7,(11)(12)(13)(14)(15)(16)(17). Recent studies confirm that this technique may be very attractive for dermatophyte identification (18-22).…”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a reliable technique for the identification and typing of microbial pathogens such as bacteria (2-7), yeasts (8-10), and filamentous fungi, including dermatophytes (7,(11)(12)(13)(14)(15)(16)(17). Recent studies confirm that this technique may be very attractive for dermatophyte identification (18-22).…”
mentioning
confidence: 99%